The Role of Teachers in Enhancing Qur’anic Literacy at Madrasah Diniyah Tarbiyatulhidayah - Luthfiyyah, Wardah; Noor, Wahyudin; Mutia, Utin (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The background of this research is the researcher's view regarding the lack of Qur'anic literacy, which necessitates that students engage in Qur'anic literacy. However, what the researcher observed during school observations indicates that students have been engaging in literacy. This raises the researcher's concern about the role of teachers in fostering Qur'anic literacy at Madrasah Diniyah Tarbiyatulhidayah. The issue raised in this research is about the role of teachers in improving students' Qur'anic literacy. The objective of this research is to understand the role of teachers in enhancing students' Qur'anic literacy. The method used in this research employs a descriptive qualitative method. The sources of data used are primary and secondary data. And the collection techniques used were observation, interviews, and documentation. After conducting the research, it was found that there are several roles used by teachers in improving Quran literacy. The roles of the teacher used include the role of the teacher as a facilitator, as a guide, as an educator, a motivator, and an evaluator.In improving literacy, teachers provide adequate facilities in terms of place and time, encourage students to habitually read several surahs from the Qur'an at the beginning of each lesson, offer special guidance with additional time and materials related to the Qur'an for students both individually and in groups, and provide extra training for some students who have difficulty in literacy of the Qur'an.